1996
DOI: 10.1007/bf02188953
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative EEG analysis during motor function and music perception in Tourette's syndrome

Abstract: Gilles de la Tourette's syndrome (TS) is a neurobehavioral disorder of childhood onset that is characterized by motor and vocal tics and associated behavioral disturbances including obsessive-compulsive symptoms. We performed 30 channel quantitative electroencephalograms (EEGs) on 13 Tourette patients and 26 controls and studied both resting and manumotor/music perception activation conditions. Resting EEGs did not show any differences between patients and controls, as known from the literature. However, durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 22 publications
2
7
0
Order By: Relevance
“…Their decrease in alpha was mainly on the temporal areas and our findings of the changes in alpha activity on the central areas were not statistically significant. The results of Gunther et al (20) of a decrease in brain activation on the temporal and parietal areas during music perception are also consistent with our decreases in activity, as is their lower alpha activity associated with improvement in spatial testing. Our increase in delta activity on the frontal midline areas is consistent with the results of Petsche et al (21) who reported the frontal midline area most involved in increased coherence patterns when a professional violin-cellist was playing scales.…”
Section: Acute Effect On Epileptiform Activitysupporting
confidence: 93%
“…Their decrease in alpha was mainly on the temporal areas and our findings of the changes in alpha activity on the central areas were not statistically significant. The results of Gunther et al (20) of a decrease in brain activation on the temporal and parietal areas during music perception are also consistent with our decreases in activity, as is their lower alpha activity associated with improvement in spatial testing. Our increase in delta activity on the frontal midline areas is consistent with the results of Petsche et al (21) who reported the frontal midline area most involved in increased coherence patterns when a professional violin-cellist was playing scales.…”
Section: Acute Effect On Epileptiform Activitysupporting
confidence: 93%
“…A number of studies have examined EEG microstates during active tasks such as motor function and auditory processing (e.g. Günther et al, 1996), or during cognitive tasks (e.g. Stevens et al, 1997), in addition to event-related studies examining microstates time-locked to a stimulus (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have analyzed microstates in the mu rhythm (8∼12 Hz) of EEG [ 11 , 12 , 36 ], but most were based on a wider frequency band, such as 2∼20 Hz [ 36 ] or 1∼40 Hz [ 12 ]. The existing research results have shown that there is no significant correlation between the 4 typical microstates and the frequency band [ 11 ].…”
Section: Methodsmentioning
confidence: 99%
“…Our research was based on delta (1∼4 Hz), theta (14∼20 Hz), alpha (8∼14 Hz), beta (14∼20 Hz), and gamma (20∼40 Hz) frequency bands. Firstly, we calculated the average power of all EEG acquisition channels in each frequency band, and then we calculated the cross correlation coefficient (Pearson's R ) [ 12 ] between the microstate and frequency band according to following formula: where x i and y i represent the GFP of the microstate and the average power of each frequency band, respectively; i is the length of the data analyzed (variables) ( i =1, 2, …, n ); and are the means of the 2 variables; ρ xy is the correlation coefficient of the 2 variables and can measure the degree of correlation and correlation properties of the 2 variables. The value of | ρ xy |(| ρ xy | ≤ 1) reflects the correlation degree of the 2 variables, and the greater the value the stronger the degree of correlation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation